2022
DOI: 10.1039/d1fo04109f
|View full text |Cite
|
Sign up to set email alerts
|

Corn distillers solubles as a novel bioresource of bioactive peptides with ACE and DPP IV inhibition activity: characterization, in silico evaluation, and molecular docking

Abstract: The study aimed to investigate the biological potential of underutilized and low-value corn distillers solubles, containing a unique unexplored blend of heat-treated corn and yeast proteins, from bioethanol industries, by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(154 reference statements)
1
3
0
Order By: Relevance
“…18,34 The positive inhibitors including IPI, sitagliptin, and omarigliptin were chosen to test the molecular docking methods, and the results showed that IPI, sitagliptin, and omarigliptin had a lower average binding energy with Δ G values of −6.04 ± 0.53, −7.12 ± 0.54, and −7.38 ± 0.41 kcal mol −1 , respectively (Table S2†). Notably, the minimum binding energy (Δ G min ) of sitagliptin was −8.10 kcal mol −1 , which was close to the binding energy of sitagliptin reported by Sharma et al 35…”
Section: Resultssupporting
confidence: 85%
“…18,34 The positive inhibitors including IPI, sitagliptin, and omarigliptin were chosen to test the molecular docking methods, and the results showed that IPI, sitagliptin, and omarigliptin had a lower average binding energy with Δ G values of −6.04 ± 0.53, −7.12 ± 0.54, and −7.38 ± 0.41 kcal mol −1 , respectively (Table S2†). Notably, the minimum binding energy (Δ G min ) of sitagliptin was −8.10 kcal mol −1 , which was close to the binding energy of sitagliptin reported by Sharma et al 35…”
Section: Resultssupporting
confidence: 85%
“…Enzymatic hydrolysis considerably improves the solubility and functional characteristics of CGM, and the corn peptides also have a variety of potential biological effects. 19,20 Helicobacter pylori can adhere to and colonize GES-1 cells through specific binding between adhesins on the H. pylori surface and receptors on GES-1 cells. Studies have reported that some polysaccharides could inhibit H. pylori adhesion to GES-1 cells as receptor analogs or adhesin analogs.…”
Section: Resultsmentioning
confidence: 99%
“…It mostly consists of zein and glutelin and has poor solubility, which restricts its range of applications. Enzymatic hydrolysis considerably improves the solubility and functional characteristics of CGM, and the corn peptides also have a variety of potential biological effects 19,20 …”
Section: Resultsmentioning
confidence: 99%
“… Kaczmarek et al (2014) and Ghazi et al (2002) found no difference in growth and yield in broiler chicks administered protease-supplemented feed, which may result from the higher rate of starch digestion in the upper gastrointestinal tract. Maize has been discovered to contain protease and some other inhibitors ( Sharma et al , 2022 ). The poly functional Hageman factor inhibitor derived from maize inhibited endogenous protease and amylase activity, which resulted in poor growth performance ( Choct et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%